The Impact of Socially Responsible Investing in European Markets: Evidence of the Global Financial Crisis - Guia Arraiano, Irene (European Journal of Sustainable Development, 2018)
The increasing global importance of the environmental, social and economic aspects and the high complexity of their implications at the corporate level is the reason for an intense and extensive research activity, leading Socially Responsible Investing to a current and prominent theme, namely in Europe. In this context, this study analyses the effects of Socially Responsible Investing on portfolio performance of all listed firms on the ten most important European stock markets over the period 2001-2013 rated by the Global Reporting Initiative. In order to measure the portfolios’ performance, a market model and a four-factor model are applied in which risk factors were constructed for the markets under study. A relevant finding of the present study is that investing in this type of firms before the financial crisis was less risky than investing afterwards, as it presented to be riskier. Nevertheless, investing in socially responsible firms which had a higher profitability in the past outperforms the market. However, the results show the existence of market singularities across European countries that must be considered, as well as the periods of pre and post global financial crisis that affected the European stock markets, triggered the sovereign debt crisis, especially in peripheral countries. Keywords: European stock markets, Socially Responsible Investing, Global Reporting Initiative, performance, risk, financial crisis.